(untitled) (Scientia Agricola, 2020)
The evaluation of factors that affect glucosinolates (GLS) concentrations in the roots, leaves, and inflorescence of broccoli plants is important in the improvement of the concentration of bioactive compounds and thus in the enhancement of the nutritional properties. In this work, the yield and the concentration of GLS of seven broccoli cultivars (Brassica oleracea var. italica) grown under salinity in field conditions were studied during three different seasons (autumn, winter, and spring). The results show that, generally, salinity did not alter significantly the inflorescence yield during any of the seasons, indicating a high tolerance of the cultivars tested. Yield was reduced only in cultivar Gea in autumn and in cultivar Parthenon in spring. The distribution of the GLS showed that their accumulation was greater in inflorescences and leaves, with higher concentrations in autumn and spring. The activation of GLS synthesis by salinity was restricted to several cultivars and depended on the season, with no reductions compared to control plants. In this study, we discuss the appearance of a Cinnamoyl-indol-GLS derivative in some of the cultivars and seasons with higher incidence in NaCl-treated plants.